Y the last man. - Vaughan, Brian K. (DC Comics, 2009)
Yorick, Dr. Allison Mann, and agent 355 continue their search for a cure to the plague that killed every being with a Y chromosome except Yorick while evading the man-hating Daughters of the Amazon, unaware that Yorick's sister is a member.